Assemble of Bi-doped TiO2 onto 2D MoS2: an efficient p–n heterojunction for photocatalytic H2 generation under visible light. (15th February 2021) - Bera, Susmita; Kumari, Ankita; Ghosh, Srabanti; Basu, Rajendra N
Abstract: Fabrication of noble-metal-free, efficient and stable hybrid photocatalyst is essential to address the rapidly growing energy crisis and environmental pollution. Here, MoS2 has been used as the co-catalyst on Bi-doped TiO2 to form a novel heterostructure to increase the utilization of the photogenerated charge carriers for improving photocatalytic H2 evolution activity through water reduction. Significantly increased photocatalytic H2 generation has been achieved on the optimized MoS2 /Bi-TiO2 nanocomposite (∼512 μ mol g –1 ) after 4 h of visible light illumination, which is nine times higher than that of the pristine TiO2 (∼57 μ mol g –1 ). The measurements of photocurrent, charge transfer resistance and photo-stability of MoS2 /Bi-TiO2 photoanode imply that charge separation efficiency has been improved in comparison to the pure MoS2 and TiO2 photoanodes. Further, the Mott–Schottky study confirmed that a p–n heterojunction has been formed between n-type MoS2 and p-type Bi-doped TiO2, which provides a potential gradient to increase charge separation and transfer efficiency. On the basis of these experimental results, this enhanced photocatalytic activity of MoS2 /Bi-TiO2 heterostructures could be ascribed to the significant visible light absorption and the efficient charge carrier separation. Thus, this work demonstrates the effect of p–n junction for achieving high H2 evolution activity and photoelectrochemical water oxidation under visible light illumination.